2017
DOI: 10.2174/1874192401711010028
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of the Syntax Score in Patients With Chronic Coronary Artery Disease Undergoing Percutaneous Coronary Intervention or Coronary Artery Bypass Grafting: A Pilot Study

Abstract: Objectives: To evaluate the usefulness of the SYNTAX score (SS) in predicting 1-year clinical outcomes in a population of patients with chronic coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG).Background:Despite the proven prognostic value of the SS in patients with multivessel and/or left main (LM) CAD, its usefulness in other patient subsets remains uncertain.Methods: This was a prospective single centre cohort study conducted from Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Presence of CAS has been shown to be a significant risk factor for peri-post-operative stroke in patients undergoing CABG, with a prevalence of 3% in unilateral stenosis, 5% in bilateral stenosis, and 7% in total carotid occlusion. [10,31,32] Therefore, screening for CAS before CABG in patients with intermediate and high SS may be reasonable. In conclusion, we demonstrated that there was a proportional increase in the severity of CAS to CAD complexity using SS.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of CAS has been shown to be a significant risk factor for peri-post-operative stroke in patients undergoing CABG, with a prevalence of 3% in unilateral stenosis, 5% in bilateral stenosis, and 7% in total carotid occlusion. [10,31,32] Therefore, screening for CAS before CABG in patients with intermediate and high SS may be reasonable. In conclusion, we demonstrated that there was a proportional increase in the severity of CAS to CAD complexity using SS.…”
Section: Discussionmentioning
confidence: 99%
“…Селективну поліпозиційну коронаровентрикулографію (КАГ) проводили за методикою M. Judkins (SIEMENS Axiom Artis, Німеччина) для оцінки ступеня звуження просвіту інфарктзалежної вінцевої артерії, локалізації стенозу та кількості ураження судин за шкалами SS I, SS IІ. Тяжкість анатомічного ураження ВА визначали за шкалою "SYNTAX": анатомічні ураження вважали легкими у разі нарахування ≤ 22 балів, помірні -23-32 бали і тяжкі -≥33 балів [24].…”
unclassified